The Project of Artistic Workshops with Students: Achievements and Challenges of Participatory Practice in University Curriculum - Sasin, Magdalena (Participatory Social Work: Research, Practice, Education, 2019)
The paper deals with the issue of participatory practice of students, presented on the basis of the project Artistic Interventions: Self-Development Through Art. It was conducted among students of the University of Łódź, Faculty of Educational Sciences, in the academic year 2015/2016. The assumptions and proceedings of this project were presented through the lens of participatory practice in the academic environment. The workshops offered within the project met the repeatedly expressed self-educational artistic needs of students. The shortage of such classes was one of the main findings that emerged from research on self-education carried out by the author among students at the Faculty of Educational Sciences, University of Łódź, in 2012. The research was carried out using the dialogue method, utilising a group interview technique. Observations made by the author during the organization of workshops, enrolment, classes and preparation for the final concert and exhibitions of Artistic Interventions were tested out against the remarks and experiences of the teachers conducting the workshops. Unexpectedly, offering supplemental, voluntary self-educational activities posed some problems. Although organizing free of charge artistic classes for students is not easy, even achieving this appears not to be sufficient. Creating and sustaining participatory practice among students seems to be essential. This practice would, in the long term, result in increasing their activity and responsibility for their educational process. This situation is related to the issue of staff participation that is more and more often mentioned in the context of university education in Poland.